Invitro activity of T4 bacteriophage on uropathogenic e. Coli - Almanseekaana, Limes Husam; Mustafa Mahmoud, Mohammed Imad Al-Deen (IIUM Press, 2017)
Bacteriophage is a virus that infects bacteria and can kill a bacterial cell or integrate its nucleic acid (DNA or RNA) into the host bacterial cell. One of the phage important medical applications is using it as an alternative approach to treatment of infections by resistant pathogenic bacteria. This book aims to review the literature concerning the use of bacteriophages for the treatment of clinical bacterial infections and emphasizing our own research findings on the susceptibility of drug resistant uropathogenic E. coli towards the T4 phage. The study involved collection of resistant uropathogenic E. coli (UPEC) toward (Ceftazidime, Gentamicin, Trimethoprim/Sulfamethoxazole, Ampicillin, Amoxicillin with Clavulanic Acid and Ciprofloxacin,) isolates from (Hospital Tengku Ampuan Afzan) HTAA, Kuantan, Pahang during a 4 months period (from 01/September/2015 to 31/December/2015). Re-identification of UPEC isolates was done by scientifically approved conventional diagnostic methods. To store isolates for further laboratory procedures, approved long term and short term bacterial storage methods were followed. All UPEC isolates were checked for antimicrobial susceptibility test by the Kirby & Bauer method and by the extended spectrum beta-lactamase (ESBL) screening test. The quantitation of T4 bacteriophage was done at first by the plaque assay on reference E. coli strain ATCC25922. In the plaque assay for UPEC, serial log dilutions of T4 phage (1 × 10-1, 1 × 10-2, 1 × 10-3 , 1 × 10-4 ,1 × 10-5 , 1 × 10-6 , 1 × 10-7 , 1 × 10-8 , 1 × 10-9 and 1 × 10-10( were incubated with UPEC by using the double agar layer technique. Countable plaques were formed for all UPEC isolates in plates inoculated with phage dilutions of 1 × 10-6 and 1 × 10-7. To determine the phage Minimal Inhibitory Concentration (phage MIC), the microbroth dilution method was performed. The phage MIC for the bacterial isolates was ~1 × 105/mL which is the lowest phage concentration or highest dilution which gave a clear broth (no bacterial growth). Serotyping of UPEC H & O antigens was done by standard agglutination method. The percentage distribution of UPEC serotypes was CAN55 (14%), MSHS94 (6%) and MSHS23a (10%) and unknown serotype (70%). In conclusion, the T4 phage concentration of 1 × 105/mL is regarded as the phage MIC for all the tested UPEC strains showing a lytic effect against UPEC.